The effect of an educational approach based on Schmidt’s Schema Theory on learning some basic tennis skills - Rahim , Haider Radhi; Hawash, Dhabyaa Jafer; Jasim , Aghader Hadi (Journal of Physical Education, 2026)
The research seeks to develop an educational curriculum based on Schmidt’s Schema Theory for acquiring fundamental tennis skills, implement this curriculum, and assess its impact on the learning of these skills. The researchers employed the experimental technique by configuring the experimental and control groups to align with the nature of the issue. The research sample comprised tennis players aged 11 to 13 years, categorized into a primary experimental group of 20 players, alongside a control group and an experimental group system. The control group comprised 10 participants, and the experimental group also consisted of 10 participants. The exploratory experiment group consisted of three participants, while three players were removed for lack of commitment. The investigators ran a pilot study on 8 July 2025, with three participants. Subsequently, the research sample was given pre-tests in two days (the first day on October 7th, 2025) by using a serve skill test and for backhand driving skills. The main experiment was carried out for a period of 8 weeks, with three lessons per week. Subsequently, the post-tests were administered, using identical methods regarding timing, location, instruments utilized, and the preparation of all conditions surrounding the pre-tests, to mitigate variables that could influence the post-test outcomes. Subsequently, the results were statistically analyzed, tabulated, and scientifically examined, culminating in conclusions and recommendations.